Peran Guru Bimbingan Konseling dalam Menangani Perubahan Perilaku Remaja di Lingkungan Sekolah: Studi Kasus SMP Negeri 21 Batanghari - Sukatin, Sukatin; Ariyanto, Masyhudi; Agnesia, Tiara; Warahmah, Mawaddataw; Sartika, Diah Dwi; Awana, Mardiatun (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
This study investigates the role of Guidance and Counseling (BK) teachers in addressing adolescent behavioral changes at SMP Negeri 3 Kediri. Utilizing a qualitative research approach, data were gathered through observations, interviews with BK teachers, students, and school principals, as well as documentation analysis. The findings indicate that various factors, including family dynamics, peer influence, and academic pressure, contribute to behavioral shifts among students. BK teachers employed individual counseling, group counseling, and cognitive-behavioral therapy techniques, demonstrating effectiveness in enhancing students' self-confidence, emotional regulation, and academic motivation. However, challenges such as limited parental involvement and time constraints in counseling sessions persisted. Despite these limitations, active student participation in counseling programs significantly influenced their behavioral improvement. The study highlights the need for stronger collaboration between BK teachers, school administrators, and parents to optimize the effectiveness of counseling services in schools.